Las imágenes y las cosas en las post-dictadura argentina: pertenencias, símbolos, simulacros (Altre Modernità, 2021)
This essay aims to investigate the representation of objects in post-dictatorship photography and Argentine visual arts. Based on the thought of the Italian philosopher Remo Bodei about the difference between ‘object’ and ‘thing’, we maintain that this opposition serves, as a theoretical framework, to deepen the analysis of the visual representations of objects and to understand the apparent paradox that these images conceal: a visuality that works only in mutual interdependence of the language. The works of some of the most outstanding post-dictatorship photographers and artists are analyzed: Marcelo Brodsky, Fernando Gutiérrez, Paula Luttringer, Helen Zout, Gabriela Bettini, Inés Ulanovsky, Julio Pantoja, Martín Kovensky, Omar Estela et al.
Keywords: Photography; Visual Arts; post-dictatorship; memory; objects